Pemanfaatan Cfd Fluent/Uns 4.1.9 Dalam Perbaikan Desain Bilah Impeler Pompa Sentrifugal Produk Lokal - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Kedokteran Gigi UGM, 2002)
This research is aimed at improving the design of a locally produced centrifugal pump NS-50 by the use of CFD (Computational Fluid Dynamics) Fluent/uns version 4.1.9. Four factors involved in this study: blade number, thickness, inlet angle 131, and outlet angle 132. Original pump has 6 blades with 5 mm thickness, and /3, = 132 = 41,4". Optimization is targetted to achieve the highest efficiency possible by applying Response SurfaceM , Method P is (RSM). An hydraulic index of power, imp and pT is fficiency, 1P, defined as (E/E reference ) x (P/Preference )x(11T,reference/RT ) where E is e turbulence-viscosity-ratio, is used as a measure of improvement. Original design's 1P is set to 1. The improved design achieved with blade number 7, 131 = 41.40" (tolerance â10%), 132 = 32.99' (tolerance +10%), and blade thickness 5.7540.75 mm is obtained with 24 observations only and IP value of 1.732.